Roles of DegP in prevention of protein misfolding in the Periplasm upon overexpression of penicillin acylase in Escherichia coli - Pan, K. L.; Hsiao, H. C.; Weng, C. L.; Wu, M. S.; Chou, C. P. (Journal of Bacteriology, 2003)
Enhancement of the production of soluble recombinant penicillin acylase in Escherichia coli via coexpression of a periplasmic protease/chaperone, DegP, was demonstrated. Coexpression of DegP resulted in a shift of in vivo penicillin acylase (PAC) synthesis flux from the nonproductive pathway to the productive one when pac was overexpressed. The number of inclusion bodies, which consist primarily of protein aggregates of PAC precursors in the periplasm, was highly reduced, and the specific PAC activity was highly increased. DegP was a heat shock protein induced in response to pac overexpression, suggesting that the protein could possibly suppress the physiological toxicity caused by pac overexpression. Coexpression of DegP(S210A), a DegP mutant without protease activity but retaining chaperone activity, could not suppress the physiological toxicity, suggesting that DegP protease activity was primarily responsible for the suppression, possibly by degradation of abnormal proteins when pac was overexpressed. However, a shortage of periplasmic protease activity was not the only reason for the deterioration in culture performance upon pac overexpression because coexpression of a DegP-homologous periplasmic protease, DegQ or DegS, could not suppress the physiological toxicity. The chaperone activity of DegP is proposed to be another possible factor contributing to the suppression.